О принципе кососимметрии - Никитина, Н.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The principle of skew-symmetry which can be applied as a criterion of the existence of periodic solutions is presented. The example of a limiting cycle with skew-symmetry is given.